TWO STEPS OF RICARDIAN EQUIVALENCE: AN EVIDENCE IN INDONESIA - ADHITYA WARDHONO; AGUS FERDIANTO; M. ABD. NASIR; CIPLIS GEMA QORI'AH (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
Ricardian Equivalence was analyzed through the influence of deficit fiscal policy on consumption, the fiscal deficit policy of Soeharto regime and reform had a difference, the difference lied in the policy as outline in the government budgets preparation. Soeharto regime applied budget concept of the T-account model, while the reform applied budget concept of I-account. The differences of concept budgetting affected the deficit fiscal policy, while the component of deficit fiscal policy consisted of budget deficits, government expenditure, government debt, and tax revenue. The purpose of this paper is to determine the effect of the differences in Soeharto regime and reform toward deficit fiscal policy component, as well as to determine the effect of deficit fiscal policy to domestic consumption, and determine the Ricardian Equivalence phenomenon and formation. Based on these objectives, an analysis tool used was Ordinary Least Squared (OLS) and Two Stage Least Squared (TSLS), with time series data from the years 1969-2013. The analysis showed that the difference reign did not significantly affect the components of deficits fiscal, and Ricardian Equivalence happened in Indonesia by the year 1969-1981 as Ricardian first period, and 1982-2013 as the second period of Ricardian.